Análise comparativa do potencial alelopático do extrato hidroalcoólico e do óleo essencial de folhas de cipó-d'alho (Bignoniaceae) - SOUZA FILHO, Antonio Pedro da Silva (2013)
Allelopathy is an important mechanism that affects the stability of agro-eco systems. The identification of this character, in several cases, is accomplished via analysis of the effects of polar crude extracts. The allelopathic activity of the species "cipó-de-alho"(Mansoa standleyi - Bignoniaceae) is characterized in the present work, by comparing the effects of the hydroalcoholic extract and essential oil of the leaves, attempting to establish the need to consider in research of this nature the approach involving non polar extracts. Bioassays of the weed plant 'malicia'' (Mimosa pudica) radicle and hypocotyl germination and growth were carried out in periods of 10 days, using concentrations of 0.5%; 1.0% and 2.0%. The chemical constituents of the essential oil were also identified. The results showed that both the hydroalcoholic extract and the essential oil have the potential to inhibit radicle and hypocotyl germination and growth. The hydroalcoholic extract showed higher potential to inhibit germination, while the essential oil promoted more intense inhibitions on radicle and hypocotyl growth. The effects were positively related with concentration, with maximum and minimum effects being obtained at concentrations of 2.0% and 0.5%, respectively. The sulfur compounds diallyl disulfide (42.15) and diallyl trisulfide (11.25%), alone or in association, are involved with the allelophatic effects caused by the essential oil. In addition, the results point to the need to consider using non polar extracts when evaluating the allelopathic activity of a given plant, especially when there is no information about the production of essential oil by the prospected plant.